2017
DOI: 10.1016/j.ijsu.2017.09.076
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and prognostic significance of FoxM1 in gastric cancer: A meta-analysis

Abstract: Expression of FoxM1 is associated with TNM stage, depth of invasion, lymph node metastasis and poor prognosis of the patients with GC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Gastric cancer is the second most significant reason for global cancer-related mortalities [44], [45] and the fifth most prevalent cancer in the world [46], [47]. In the United States, there are about 7.4 new cases of gastric cancer per 100,000 women and men per year [48].…”
Section: The Role Of Pirnas In Cancermentioning
confidence: 99%
“…Gastric cancer is the second most significant reason for global cancer-related mortalities [44], [45] and the fifth most prevalent cancer in the world [46], [47]. In the United States, there are about 7.4 new cases of gastric cancer per 100,000 women and men per year [48].…”
Section: The Role Of Pirnas In Cancermentioning
confidence: 99%
“…19,47,48 The first meta-analysis included eight studies involving 529 patients with gastric cancer. 47 The meta-analysis demonstrated that the levels of FOXM1 were associated with TNM stage (odds ratio [OR] ¼ 0.482; 95% CI 0.275, 0.845; P ¼ 0.011), depth of invasion (OR ¼ 0.617; 95% CI 0.382, 0.998; P ¼ 0.049), lymph node metastasis (OR ¼ 2.084; 95% CI 1.305, 3.328; P ¼ 0.002) and 5-year overall survival (OR ¼ 0.180; 95% CI 0.095, 0.341; P < 0.001). 47 Another meta-analysis studied the prognostic value of FOXC1 in various cancers from 16 studies and demonstrated a statistically significant association between FOXC1 protein levels and survival (HR ¼ 1.186; 95% CI 1.122, 1.255; P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…45,46 Three previous systematic reviews have outlined the relationship between levels of the FOX family members and outcomes in multiple cancer types. 19,47,48 The first meta-analysis included eight studies involving 529 patients with gastric cancer. 47 The meta-analysis demonstrated that the levels of FOXM1 were associated with TNM stage (odds ratio [OR] = 0.482; 95% CI 0.275, 0.845; P = 0.011), depth of invasion (OR = 0.617; 95% CI 0.382, 0.998; P = 0.049), lymph node metastasis (OR = 2.084; 95% CI 1.305, 3.328; P = 0.002) and 5-year overall survival (OR = 0.180; 95% CI 0.095, 0.341; P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, FoxO1 can promote lipolysis by upregulating the expression of fatty triglyceride lipase. 50 FoxM1 is indispensable for normal cell proliferation, highly expressed in many cancers 51 , 52 , 53 and closely associated with poor prognosis. One of the mechanisms by which FoxM1 promotes tumor development is the reprogramming process of cell metabolism.…”
Section: Drivers Of Metabolic Reprogramming: Related Genes Proteins A...mentioning
confidence: 99%